Morphometric Analysis of the Balakh valley basin in the Sharbažir area an applied study - Mohammed, Asst.Prof.Dr. Khalil Karim Mohammed (Sulaimani Journal for Humanities, 2025)
This study aims to analyze the morphometric properties of the "Wadi Balkh" basin. In order to reach the goal of the study, the spatial statistical analysis method was used through the analysis of the digital elevation model (DEM12.5m) and using the geographic information systems technology (ArcGIS 10.8). Doing so, the values of the variables and morphometric measurements of the study area were reached, such as the topographic characteristics, area, shape of the basin and the river network of the region, in addition to the analysis of the hypsometric curve and hypsometric integration, which is a time scale to show the erosion stage of the basin. Through this study, the researcher was able to build a database for the morphometric characteristics of the "Balkh Valley" basin. Based on this, the researcher concluded that the area of the region is (164.55 km2) and its length is (27.16 km). The basin tends to be rectangular in shape with a value of (0.53), which leads to reducing the occurrence of floods at the ends of the valley. The ruggedness ratio is (61.4), while the hypsometric integration is (31%), meaning that the basin has reached an advanced stage in its erosion cycle. The study also showed that there are (82) waterways in the valley combined in (4) river ranks, the lengths of the channels reached (133.27 km), while the longitudinal discharge density reached (0.81 km/km2).
Keywords: Balkh Valley Basin; Morphometric Analysis; Hypsometric Integral; Hypsometric Curve